2010
DOI: 10.1007/s00296-010-1600-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid predicts changes in reports of non-gouty chronic pain: a prospective study among women with inflammatory and non-inflammatory pain

Abstract: Widespread pain has earlier been associated with an increase in serum urate (SU). The aim of this study was to longitudinally study the relation between changes in pain reporting and the level of SU among women with chronic pain. Consecutive female patients (n = 124; aged 20-70 years), at rheumatology and rehabilitation practices, with chronic musculoskeletal pain of different origins were followed for 1 year with repeated blood samples and questionnaires. Complete data were obtained from 107 individuals. Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…A comparison of urate levels demonstrated consistently higher urate levels in patients experiencing joint pain than in pain-free patients, independent of gender and across the relevant age group >40 years, which covers the broad majority of this population. A similar relationship between urate level and musculo-skeletal pain was indicated in a 1-year longitudinal study linking urate levels in women with chronic non-gouty pain to the number of pain locations [16]. The authors suggested more intensive care and rehabilitation measures for patients featuring a relatively high serum urate level, yet still within the reference range, along with pain at multiple locations [16].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A comparison of urate levels demonstrated consistently higher urate levels in patients experiencing joint pain than in pain-free patients, independent of gender and across the relevant age group >40 years, which covers the broad majority of this population. A similar relationship between urate level and musculo-skeletal pain was indicated in a 1-year longitudinal study linking urate levels in women with chronic non-gouty pain to the number of pain locations [16]. The authors suggested more intensive care and rehabilitation measures for patients featuring a relatively high serum urate level, yet still within the reference range, along with pain at multiple locations [16].…”
Section: Discussionmentioning
confidence: 71%
“…A similar relationship between urate level and musculo-skeletal pain was indicated in a 1-year longitudinal study linking urate levels in women with chronic non-gouty pain to the number of pain locations [16]. The authors suggested more intensive care and rehabilitation measures for patients featuring a relatively high serum urate level, yet still within the reference range, along with pain at multiple locations [16].…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, Andersson and Leden, in a prospective study of 124 women, found a relationship between serum uric acid level and musculoskeletal pain, with a significant association between urate level and chronic nongouty pain in women [27].…”
Section: Discussionmentioning
confidence: 82%
“…In the present literature, it is well established that hyperuricemia plays an important role in the manifestation of gout, but whether it can also cause plantar fasciitis has not been studied thus far, nor whether AH alone is an indication to start anti-gout treatment. It is equally well established that the degree of hyperuricemia is a strong predictor in developing gout [26][27][28], but whether hyperuricemia also plays a role in the development of plantar fasciitis has not yet been studied. However, Nossent et al noted that despite the high prevalence of hyperuricemia (10.7% of the population), uric acid was not independently predictive of cardiovascular disease or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in adult women about GCP and the increase in pain locations shows a significant correlation with the increase in uric acid plasma concentrations after a one-year follow-up, recognizing this combination as a risk factor for the expansion of inflammatory and non-inflammatory pain [21].…”
Section: Generalized Chronic Pain (Gcp)mentioning
confidence: 93%